PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP MOTIVASI KARYAWAN STASIUN METEOROLOGI KLAS II AHMAD YANI SEMARANG - satrio aji prabowo (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of influence leadership style democratic ,organizational culture and compensation on employee motivation Meteorological stationclass II Ahmad Yani. This research is a quantitative research. Variable democratic leadershipstyle, organizational culture, compensation and motivation. The population in this study areClass II Meteorological Station Ahmad Yani represented by one person, namely the Head ofTu as respondents. The data collection is done directly by using a questionnaire containing35 questions. Using data analysis tools and multiple regression. In this study, the number ofsamples (n) = 40 and the amount can be calculated 40-2 df = 38 to df = 38 and alpha = 0.05table obtained r = 0.320, results showed that the multiple linear regression equation is Y = -0,059X1 X2 + 1.068 - 0.039 X3, and alpha = 0.05, thus the democratic leadership style andnot significant negative effect of employee Meteorologo stations class II Ahmad Yanimotivation, Because the value of b1 = -0.059 and sig> 0.05 (0.325 > 0.05), OrganizationalCulture and significant positive effect of employee Meteorologo stations class II Ahmad Yanimotivation, Because the value of b1 = 1.068 and sig <0.05 (0.000 <0.05), and theCompensation negative and not significant of employee Meteorologo stations class II AhmadYani motivation, Because the value of b1 = -0.039 and sig> 0.05 (0.299> 0.05).Simultaneously, the Democratic leadership style, organizational culture and compensationeffect on motivation, because the test results amounted to 765.926 with significant F 0,000.R2 as well as from the results of the Democratic leadership styles, organizational cultureaffects motivation and compensation of 98.3%, this implies that there are other variables thataffect motivation at 1.7%